De l’activité DE simulation à l’activité EN simulation : simuler pour stimuler - Marc-Éric Bobillier Chaumon; Sabrina Rouat; Elsa Laneyrie; Bruno Cuvillier (Activités)
The purpose of this paper is to propose a functional and diachronic taxonomy of the different simulation types that the study day, devoted to the simulation process (organized by the Review “Activities”), made it possible to highlight. This categorization is based on four main orientations of the staging of the activity that can relate respectively to the simulation of a situation (i) to come (prospective or predictive simulation), (ii) to become (constructive or reflexive simulation), (iii) alive or persistent (projective simulation) and (iv) past (retrospective simulation). For each of these approaches, we will outline the main associated methods and discuss their respective contributions and limitations.